Kapapagaria Muslim-Christian brotherhood [videorecording] - Jacob, Marilou ([Manila] Communication Foundation for Asia, 1997)
A documentary on Muslim culture, shot in Zamboanga, Maharlika Village and the Quiapo Mosque, it takes a first step towards understanding by breaking down myths about Muslims. With interviews of Muslims and non-Muslims and an expert from the UP Institute of Islamic Studies.
Keywords: Muslims -- Philippines; Sociology